The Orphic Theogonic Poems Attributed to Linos. Notes on the Testimony of Pausanias - Sobolewska, Mariola (Collectanea Philologica, 2017)
I will discuss the connection between Linos and Orphics as it is outlined in the Description of Greece. Pausanias writes that Linos propagated in his songs the genealogy of the first deities of the Greek pantheon. According to Pausanias, this genealogy was similar to the one in Hesiod’s Theogony. Pausanias himself believed that the majority of Linos’ works were inauthentic. He was of the opinion that if Linos wrote anything, none of it has survived. However, no one has tried to explain why so many works were attributed to Linos. In my article I try to answer to this question.